Efektivitas Metode Sosialisasi melalui Ganjaran dan Hukuman pada Perilaku Anak Asuh Remaja di Lembaga Kesejahteraan Sosial Anak Kota Padang - Anggraini, Nini; Fachrina, Fachrina; Maihasni, Maihasni; Syafiola, Fedro (Universitas Medan Area, 2024)
This study aims to examine the effectiveness of socialization methods through rewards and punishments in influencing the behavior of adolescent foster children in Padang children's Social Welfare Institutions. Through a qualitative approach with interview and document analysis methods, this study explores the types of rewards and punishments applied, their impact on the behavior of foster children, as well as the factors that influence the success of these methods. The findings suggest that appropriate rewarding can reinforce positive behavior, while inappropriate application of punishment has the potential to have negative effects. However, the effectiveness of this method is also influenced by factors such as the background of foster children, the quality of human resources in institutions, and family and community involvement. This study concludes that a holistic approach is needed that includes aspects of religious education, moral development, development of social skills, as well as periodic evaluation of the coaching program. Recommendations for further research include involving more diverse data collection methods such as direct observation and documentation studies, as well as more in-depth analysis of the impact of the effectiveness of the socialization methods used. This research contributes to the understanding of the effective application of socialization methods in shaping the positive behavior of adolescent foster children in child social welfare institutions.